Perlindungan Terhadap Simpanan Pernah Tercatat Pada Bank, Bukan Suatu Keniscayaan - Ramelan, Yudha (Jurnal Hukum & Pembangunan, 2019)
Many types of crimes occur in the banking sector, which has implications for losses suffered by people who save their money in banks. One example of crime is taking deposits out from the bank by breaking the law. It causes deletion data of customer deposits from the bank's balance sheet or a list of third party funds. Customers are declared to have already received payment from the bank, and hence the agreement to deposit funds between the customer and the bank is reported to have ended. This condition can make customers’ right to get a refund of their money from the disbursement of bank assets or deposit insurance programs become lost. In general, the modus operandi of crime is falsifying the identity or signature of the customer, and the suspect of crime involves a private bank. This condition is also due to the weak function of the bank's internal control. The illicit money, whole or in part, is used to fulfill the interest of the suspect’s life, but some of them are intended to cover an illegal transaction.